2017
DOI: 10.1007/s00590-017-2034-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low back pain among health sciences students

Abstract: This study has shown high prevalence of LBP among future healthcare provider. These risk factors should be well established to minimize the prevalence of LBP among future health sciences students. Dentistry students at higher risk of developing LBP compared to other students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 14 publications
3
29
2
2
Order By: Relevance
“…Exercise was not associated with any MPS in Jordanian or Saudi Arabia students [20,54]. Furthermore, physical activity was not associated with lower back pain in Saudi Arabia university students of Medical and Health Sciences [57]. The presented study did not demonstrate a significant association between the time spent sitting and MPS.…”
Section: Musculoskeletal Pain Symptomscontrasting
confidence: 58%
“…Exercise was not associated with any MPS in Jordanian or Saudi Arabia students [20,54]. Furthermore, physical activity was not associated with lower back pain in Saudi Arabia university students of Medical and Health Sciences [57]. The presented study did not demonstrate a significant association between the time spent sitting and MPS.…”
Section: Musculoskeletal Pain Symptomscontrasting
confidence: 58%
“…In our study, the prevalence of cigarette smoking was high (among students with LBP it was 32.7%, and among students without LBP it was 17.5%), as well as in the study Hafeez et al (2013) where it was 34.5% among students with LBP, and among students without LBP it was 9.1%. In contrast, in studies where a link between cigarette smoking and LBP was not found (Algarni et al, 2017;Aggarwal et al, 2013;AlShayhan & Saadeddin, 2018;Smith et al, 2005;Haroon et al, 2018) prevalence of smoking was less than 10% in both students with and without LBP. Besides that, the lack of association between cigarette smoking and LBP in the majority of studies can be attributed to young age of medical students in whom LBP has not occurred yet: while in our study and in the study by Hafeez et al (2013), where an association between cigarette smoking and LBP was found, the average age of participants was 22 and over, in studies where this association was not found, the average age of students was less than 22 (Algarni et al, 2017; Aggarwal et al, 2013;AlShayhan & Saadeddin, 2018;Smith et al, 2005;Haroon et al, 2018;Yucel & Torun, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…The significant association between LBP and cigarette smoking in our study was supported by some authors, as they concluded that medical students who smoked were in high risk to develop LBP (Hafeez et al, 2013). However, it was reported in numerous studies that there were no significant differences among medical students in terms of smoking habits and LBP occurrence (Algarni et al, 2017;Aggarwal et al, 2013;AlShayhan & Saadeddin, 2018;Smith et al, 2005;Haroon et al, 2018). On the other hand, cigarette smoking was not examined in a study of LBP in fourth year medical students in Belgrade (Vujcic et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…However, our study´s LBP point prevalence was considerably lower than the 53.2% to 79.17% found by Awaji [ 14 ] in a review made using seven cross-sectional studies conducted in Saudi Arabia. In other recent studies also undertaken in Saudi Arabia among specific professional groups, the point prevalence of LBP found was 80% in nurses [ 10 ], 57.3% in male high school teachers [ 13 ], 55% among faculty members [ 29 ], 40.5% in medical students [ 30 ], 51.6% in taxi drivers, 31.4% in office workers [ 31 ], and 21.2% among health sciences students [ 32 ]. Hence, in most of these cases, the point prevalence was higher than in our study, which could be related to the burden of work, type of professional or academic activity carried out by each group, and poor posture at work [ 33 ].…”
Section: Discussionmentioning
confidence: 99%